The sixth international RASopathies symposium: Precision medicine—From promise to practice. Issue 3 (11th December 2019) - Gripp, Karen W.; Schill, Lisa; Schoyer, Lisa; Stronach, Beth; Bennett, Anton M.; Blaser, Susan; Brown, Amanda; Burdine, Rebecca; Burkitt‐Wright, Emma; Castel, Pau; Darilek, Sandra; Dias, Alwyn; et al.
Abstract: The RASopathies are a group of genetic disorders that result from germline pathogenic variants affecting RAS‐mitogen activated protein kinase (MAPK) pathway genes. RASopathies share RAS/MAPK pathway dysregulation and share phenotypic manifestations affecting numerous organ systems, causing lifelong and at times life‐limiting medical complications. RASopathies may benefit from precision medicine approaches. For this reason, the Sixth International RASopathies Symposium focused on exploring precision medicine. This meeting brought together basic science researchers, clinicians, clinician scientists, patient advocates, and representatives from pharmaceutical companies and the National Institutes of Health. Novel RASopathy genes, variants, and animal models were discussed in the context of medication trials and drug development. Attempts to define and measure meaningful endpoints for treatment trials were discussed, as was drug availability to patients after trial completion.